Eagle drums - Hopson, Nasug̊raq Rainey (Roaring Brook Press, 2023)
"Winter approaches, and there's much to do if Piŋa's family wants to be prepared: hunting, fishing, gathering, and more. Now, Piŋa must travel up the mountain to collect obsidian for knapping - the same mountain where his two older brothers disappeared. As he leaves, Piŋa reassures his parents that he will not succumb to the same fate as his brothers. He will return. But when he reaches the mountaintop, he is confronted by a terrifying eagle god named Savik, who gives the boy a choice: Follow me, or die like your brothers. What follows is a harrowing journey to the home of the eagle gods, where Piŋa faces unexpected trials that teach him lessons on the natural world, the past that shapes us, and the community that binds us. With beautiful full-color art, this vivid retelling of the first Messenger Feast - still celebrated today - brings to life the origin myth of how the eagle gods bestowed the Iñupiat with the gifts of music, song, dance, community, and everlasting tradition."--